2019
DOI: 10.1140/epjc/s10052-019-7315-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-eikonal corrections on azimuthal asymmetries in the color glass condensate

Abstract: We analyse the azimuthal structure of two gluon correlations in the Color Glass Condensate including those effects that result from relaxing the shockwave approximation for the target. Working in the Glasma graph approach suitable for collisions between dilute systems, we compute numerically the azimuthal distributions and show that both even and odd harmonics appear. We study their dependence on model parameters, energy of the collision, pseudorapidity and transverse momentum of the produced particles, and le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 82 publications
(99 reference statements)
1
23
0
Order By: Relevance
“…This can be easily checked by considering the single (large x) gluon exchange limit of our results, analogous to quark antiquark scattering considered in Appendix A of the last listing of [14]. Furthermore, noneikonal corrections to high energy scattering at small x have been shown to generate angular asymmetries in particle production at small x [15]. Very similarly the large x corrections to eikonal scattering considered here result in angular asymmetries, with the important difference that the asymmetries generated in our formalism will be at higher transverse momenta than the standard small x results.…”
Section: A Evaluating the Helicity Amplitudesmentioning
confidence: 68%
“…This can be easily checked by considering the single (large x) gluon exchange limit of our results, analogous to quark antiquark scattering considered in Appendix A of the last listing of [14]. Furthermore, noneikonal corrections to high energy scattering at small x have been shown to generate angular asymmetries in particle production at small x [15]. Very similarly the large x corrections to eikonal scattering considered here result in angular asymmetries, with the important difference that the asymmetries generated in our formalism will be at higher transverse momenta than the standard small x results.…”
Section: A Evaluating the Helicity Amplitudesmentioning
confidence: 68%
“…Later in [47,48], it was shown that in the weak field limit, the finite-width corrections can be interpreted as sub-eikonal corrections to the standard Lipatov vertex and multi gluon production cross section is computed with non-eikonal corrections for proton-proton collisions at mid-rapidity. The effects of non-eikonal corrections (due to finite width of the target) on two-particle correlations are studied in [49]. Apart from the aforementioned studies that focus on the finite-width corrections to gluon production at mid-rapidity to go beyond the eikonal accuracy, in [50][51][52][53][54][55][56] quark and gluon helicity distributions are derived at Next-to-Eikonal (NEik) order.…”
mentioning
confidence: 99%
“…Relaxing this assumption is necessary to access the physics of polarized measurements [257][258][259][260][261][262][263][264][265][266]. Efforts are also being carried out to study the effect of sub-eikonal contributions to various unpolarized observables [267][268][269][270][271][272] with emphasis in non-trivial azimuthal correlations. These contributions might be relevant for precise EIC and RHIC phenomenology where the energies are much less compared to LHC or LHeC.…”
Section: Theoretical Advancesmentioning
confidence: 99%